Jacques the sophist Lacan, logos, and psychoanalysis - Cassin, Barbara 1947- (Fordham University Press, 2020)
"In a highly original rereading of the writings and seminars of Jacques Lacan, together with works of Freud and others, Cassin shows how psychoanalysis, like the sophists, challenges the very foundations of scientific rationality. In taking seriously equivocations, jokes, and unfinishable projects of interpretation, the analyst, like the sophist, allows performance, signifier, and inconsistency to reshape truth"--
"This book was first published in French as Jacques le Sophiste: Lacan, logos et psychanalyse, by Barbara Cassin © EPEL, 2012"--Page facing title page
Keywords: Lacan, Jacques -- 1901-1981; Sophistik; Psychoanalyse; Lacan, Jacques / 1901-1981; Fallacies (Logic); Logos (Philosophy)